THU0153 TCZ MIGHT BE A RISK FACTOR FOR WORSENING OF ILD, PARTICULARLY OF CHRONIC ILD. (2nd June 2020) - Tanaka, A.; Owada, T.; Hasegawa, A.; Hiyama, T.; Takamura, Y.; Miyao, T.; Yamazaki, R.; Arai, S.; Maezawa, R.; Arima, M.; Kurasawa, K.
Abstract : Background: Interstitial lung disease (ILD), frequent lung involvement, determine the prognosis of patients with RA. The presence of ILD also influences the selection of RA therapy. However, it is not fully elucidated what groups of RA-ILD patients worsen ILD. Objectives: To identify the risk factors for worsening of ILD in RA patients under biological DMARD (bDAMARDs) therapy; particularly to determine whether types of bDMARDs are associated with exacerbation of ILD. Methods: A retrospective cohort study was conducted. Subjects were consecutive 91 RA-ILD patients who received HR-CT examination at starting and during bDMARDs therapy. Clinical data were collected by reviewing. ILD was diagnosed, when patients showed ground-glass opacity (GGO), consolidation, reticular pattern or honeycomb; the former two were acute and the latter two were chronic ILD lesions. The extent of each lesion was scored and recorded. When the score was increased, the lesion was judged as worsened. The incidence of exacerbation of ILD under an indicated agent was calculated as follows; the sum of (exposure period of the agent/exposure period of any agent) in patients with the exacerbation was divided by total exposure period of the agent. Results: Subjects were 36 males and 55 females with a mean age of 66.8 years. At the entry, GGO, consolidation, reticular and honeycomb were found in16, 20, 63 and 17, respectively. Acute and chronic ILD were observed in 34 and 68, respectively. ILD worsened in 35 (38.5%). Between patients with and without ILD exacerbation, no differences were found in demographics (sex, age, disease duration, the positivity for anti-CCP ab and RF) and radiographic findings of pulmonary abnormalities. Disease activities at as 1st and sequential CT examinations were similar in both groups. The incidences of the worsening of ILD varied according to bDMARDs (Fig 1 ). The incidence of total ILD worsening was high in TCZ compared to TNF and ABT. The incidence of acute ILD worsening was similar among the three groups. However, the worsening of chronic ILD was more frequently found in TCZ than other bDMARDs. The incidence of death by respiratory failure was similar in TNF, ABT, and TCZ (Fig. 2 ). Conclusion: TCZ might be a risk factor for exacerbation of ILD, particularly of chronic ILD. Disclosure of Interests: None declared